Managing an Effective English Language Laboratory in a Polytechnic - Marlina Marzuki (Studies in English Language and Education, 2014)
Polytechnic graduates are required to have applied skills as well as communication skills in English. In most of the polytechnics in Indonesia, English courses are served as compulsory courses for students and in some institutions language laboratories are established in order to support their students. To run an effective language laboratory there are, at least four aspects that need to be considered, namely lab facilities, standard operating rules, students, and lab coordinators. Of all the agents, lab coordinators are classified as internal factors that can easily be empowered by the institutions in the management of the language lab. This paper aims to discuss leadership and management roles in improving an English Language Laboratory. The discussions are based on literature reviews, personal experiences and observations gained by the author whilst working at Politeknik Negeri Lhokseumawe for the last decade plus perceptions of teachers and administrators who have worked in the lab. Regarding the leadership and management in the language laboratory there are four items that should be improved: management of leadership, professional development, rewards, and the concept of educational management.